What does rapid naming tell us about dyslexia? - Susana Araújo; Karl Magnus Petersson; Alexandra Reis; Luís Faísca (Avances en Psicología Latinoamericana, 2011)
This article summarizes some of the important findingsfrom research evaluating the relationship betweenpoor rapid naming and impaired reading performance.Substantial evidence shows that dyslexic readers haveproblems with rapid naming of visual items. Early researchassumed that this was a consequence of phonologicalprocessing deficits, but recent findings suggestthat non-phonological processes may lie at the root ofthe association between slow naming speed and poorreading. The hypothesis that rapid naming reflects anindependent core deficit in dyslexia is supported by themain findings: (1) some dyslexics are characterized byrapid naming difficulties but intact phonological skills;(2) evidence for an independent association betweenrapid naming and reading competence in the dyslexicreaders, when the effect of phonological skills was controlled;(3) rapid naming and phonological processingmeasures are not reliably correlated. Recent researchalso reveals greater predictive power of rapid naming, inparticular the inter-item pause time, for high-frequencyword reading compared to pseudoword reading in developmentaldyslexia. Altogether, the results are moreconsistent with the view that a phonological componentalone cannot account for the rapid naming performancein dyslexia. Rather, rapid naming problems may emergefrom the inefficiencies in visual-orthographic processingas well as in phonological processing.